2011
DOI: 10.3109/02813432.2011.580090
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypoglycaemia in drug-treated diabetic patients needs attention: A population-based study

Abstract: Objective. To study one-year incidence and risk factors of severe hypoglycaemias (SH) in adult drug-treated diabetic patients living in two Finnish communities. Design. The episodes of SH and their risk factors were identifi ed from local ambulance registers, from the databases of local health care units, and from patient questionnaires. Setting. The target population consisted of all drug-treated diabetic patients from the two middle-sized communities in southern Finland, altogether 1776 patients. The study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Because hypoglycemia was assessed similarly in all three studies, we suspect that the higher rates of hypoglycemia in the DISTANCE Study cohort reflect the true risk in an ethnically diverse, real-world diabetes cohort, relative to more selective trial cohorts. Population-based studies in Finnish 40 and German 41 diabetes patients reported similarly high population rates of hypoglycemia. Glycemic targets based on data from highly selected populations with low rates of hypoglycemia may overestimate net clinical benefit for real-world patients.…”
Section: Discussionmentioning
confidence: 93%
“…Because hypoglycemia was assessed similarly in all three studies, we suspect that the higher rates of hypoglycemia in the DISTANCE Study cohort reflect the true risk in an ethnically diverse, real-world diabetes cohort, relative to more selective trial cohorts. Population-based studies in Finnish 40 and German 41 diabetes patients reported similarly high population rates of hypoglycemia. Glycemic targets based on data from highly selected populations with low rates of hypoglycemia may overestimate net clinical benefit for real-world patients.…”
Section: Discussionmentioning
confidence: 93%
“…2,[9][10][11] Although behavioral, physiologic, and therapeutic factors have been examined as causes of hypoglycemia, the authors are aware of only one study that examined the association of depression with severe hypoglycemic episodes in a population of adults with diabetes. 12 This study found that depression increased risk of hypoglycemic episodes. The study had several limitations, however, including use of an unvalidated depression measure and that data on hypoglycemic episodes were from the year before depression ascertainment.…”
Section: Introductionmentioning
confidence: 91%
“…12 A previous study found that depression was associated with self-reported hypoglycemic episodes (which included both minor and more severe episodes) in 2,718 patients with type 2 diabetes. 25 The increased risk of severe hypoglycemic episodes in patients with comorbid depression may be due to poor self-care or psychobiologic changes associated with depression.…”
Section: Depr Es Sion a Nd R Isk O F Hy P O Glycemic Epis Odesmentioning
confidence: 99%
“…They could also use these appointments to help ensure that caregivers are offered education and information about applying hypoglycemia management. Health professionals could also consider extending similar kinds of support to family members of people with type 2 diabetes using insulin or sulfonylureas, as these individuals are also vulnerable to HU and associated problems (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%